Paul, in other words a cultural reading of his letters - Neyrey, Jerome H. 1940- (Louisville, KE Westminster/John Knox, 1990)
Includes bibliographical references and index.New
Keywords: Bible. N.T. Epistles of Paul -- criticism, interpretation, etc; Sociology, Biblical